Assessment of the Perception of Benefits of Organic Gardening in Maiduguri Metropolis, Nigeria - S. B, Mustapha; U. C, Undiandeye; Y. L, Idrisa (Asian Journal of Agriculture and Rural Development, 2012)
The study examined the perception of benefits of organic gardening in Maiduguri Metropolis, Nigeria. Structured questionnaires were administered to obtain information from 166 respondents through multi-stage random and purposive sampling techniques. Data collected were analysed using descriptive statistics (frequency distribution, percentage and mean scores). The study indicates that the respondents had perceived a relatively neutral (mean score = 2.87) socio-economic benefits of organic gardening. Nevertheless, they agreed (mean score = 3.84) with the ecological benefits or organic farming. The result, equally reports that the intension of conversion to organic farming was relatively neutral (mean score = 3.49). The most important constraint to organic gardening conversion was lack of knowledge and skills regarding organic gardening. Policy recommendations were made to include: the creation of awareness on the consequences of synthetic fertilizers, pesticides among others, and adequate government support for organic gardening in the study area.